2016
DOI: 10.1016/j.ssc.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of potential-inserted quantum wells in the near infrared and Terahertz ranges

Abstract: We propose an engineering of the optical properties of GaAs/AlGaAs quantum wells using AlAs and InAs monolayer insertions. A quantitative study of the effects of the monolayer position and the well thickness on the interband and intersubband transitions, based on the extended-basis sp 3 d 5 s * tight-binding model, is presented. The effect of insertion on the interband transitions is compared with existing experimental data. As for intersubband transitions, we show that in a GaAs/AlGaAs quantum well including … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The inset shows the reciprocal space map around (224) illustrating the full relaxation state of GaP 0.67 Sb 0.33 (S x and S z are the projected coordinates in the right handed Cartesian, with the z axis parallel to the surface normal). 43 and the absence of intentional doping, the photocurrent of the GaP 0.67 Sb 0.33 grown on Si photoanode remains high compared to a reference n-doped GaP photoanode (see Fig. S7 in the ESI †) (with a much lower density of crystal defects).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The inset shows the reciprocal space map around (224) illustrating the full relaxation state of GaP 0.67 Sb 0.33 (S x and S z are the projected coordinates in the right handed Cartesian, with the z axis parallel to the surface normal). 43 and the absence of intentional doping, the photocurrent of the GaP 0.67 Sb 0.33 grown on Si photoanode remains high compared to a reference n-doped GaP photoanode (see Fig. S7 in the ESI †) (with a much lower density of crystal defects).…”
Section: Resultsmentioning
confidence: 91%
“…For these states, bowing parameters are introduced to model the strong bowing of the G bandgap of 2.7 eV. 43 With a bowing parameter equal to 9.0 eV for the s-state and equal to 2.8 eV for the p-state, the experimental bandgap for GaP 0.67 Sb 0.33 is nicely reproduced.…”
Section: Band Structure Modellingmentioning
confidence: 99%
“…This was actually implemented to shorten the operating wavelength of mid infrared QCLs . Recently, it has been theoretically shown that a three level system suitable for THz applications can be obtained in a single unbiased GaAs/AlAs QW by including multiple In and Al monolayer insertions inside the well . It was also shown that the envelope function approach (EFA), widely used in QCL modeling, fails to predict higher electron states energies in this particular case of very thin insertions, while the atomistic spds* tight‐binding (TB) model gave essentially perfect agreement with existing spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%